The impact of a PERMA model-based positive psychology intervention on fear of stroke recurrence: a randomized controlled trial - Luo, Yanfang; Su, Zhenzhen; Zhu, Lingyun; Huang, Yujuan; Liu, Zhimin; Dechen, Wangmo; Xu, Bo; Gao, Xinyu; Chen, Yuping; Qiu, Yuyu; Hao, Jianru (Frontiers in Psychology, 2025)
IntroductionThis study aimed to examine the effects of a positive psychological intervention, grounded in the PERMA model, on fear levels, psychological capital, overall well-being, and quality of life among stroke patients.MethodsA single-blind, two-arm randomized controlled trial with a repeated measures design was conducted at the Affiliated Hospital of Jiangnan University from January to December 2023. A total of 125 patients experiencing fear of stroke recurrence were randomly assigned to either the intervention group (n = 63), which received a positive psychological intervention based on the PERMA model, or the control group (n = 62), which received standard care. We assessed fear levels, psychological capital, well-being, and quality of life at baseline (T0), on the day of discharge (T1), 2 weeks post-discharge (T2), and 4 weeks post-discharge (T3). The scores of the two groups were compared post-intervention using the Generalized Estimation Equation (GEE) model to analyze the effects of time, group membership, and their interaction.ResultsThe intervention group showed statistically significant improvements compared to the control group, including reduced fear levels (T2: t = −2.094, p = 0.038; T3: t = −2.207, p = 0.029), increased psychological capital (T2: t = 2.053, p = 0.042; T3: t = 2.820, p = 0.006), enhanced well-being (T2: t = 2.037, p = 0.044; T3: t = 2.761, p = 0.007), and better quality of life (T2: t = 2.083, p = 0.039; T3: t = 2.453, p = 0.016) at both T2 and T3. Additionally, significant time-related changes were observed in fear levels, psychological capital, well-being, and quality of life (χ2 = 45.275, p < 0.001; χ2 = 37.848, p < 0.001; χ2 = 48.255, p < 0.001; χ2 = 34.231, p < 0.001, respectively). Notably, the interaction effects were statistically significant for well-being (p < 0.05).DiscussionThe PERMA-based intervention had a short-term positive effect, reducing fear levels while enhancing psychological capital, well-being, and quality of life among stroke patients.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=230313.